The Importance of Commitment as a Mediator: The Impact of Emotional Intelligence and Work Motivation on Teacher Performance - Elmi Firda Azifatul Muhibbah; Sukaris; Eva Desembrianita (Didaktika: Jurnal Kependidikan, 2024)
This research was conducted to find out things that influence teacher performance. The research aims to analyze the influence of emotional intelligence variables and work motivation variables on teacher performance variables with commitment as a mediating variable in elementary schools. The type of research used in this research is quantitative research. The population and sample in this study were elementary schools, totaling 65 respondents. The results of the research show that Emotional Intelligence has a positive and significant influence on Teacher Performance, Work Motivation has a negative and insignificant influence on Teacher Performance, Emotional Intelligence has a positive and significant influence on Commitment, Work Motivation has a positive and significant influence on Commitment, Commitment has an influence significant influence on Teacher Performance, emotional intelligence has a significant influence on Teacher Performance through Organizational Commitment, and work motivation has an influence on Teacher Performance through Commitment. From the research results, the emotional intelligence of elementary school teachers must remain good and even continue to be improved in order to achieve better teacher performance. It is hoped that teachers in elementary schools will be able to turn existing difficulties into inspiration or new sources of learning in the classroom and it is hoped that there will be teacher training to recognize the emotional intelligence that exists in teachers, which can make it easier to organize teaching and learning activities, teachers should motivate and maintaining commitment in working with the aim of achieving maximum teacher performance.